2014
DOI: 10.3892/mco.2014.326
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic bone tumors: Analysis of factors affecting prognosis and efficacy of CT and 18F-FDG PET-CT in identifying primary lesions

Abstract: Abstract.We analyzed the prognostic factors in patients with metastatic bone tumors and evaluated the efficacy of different modalities in identifying the primary lesions. A total of 145 patients with bone metastases who attended the orthopaedic outpatient clinic were included in this study. The most frequent site of bone metastases was the spine. The primary tumor type was differently distributed between patients with a known primary tumor at the first visit and those with an unknown primary lesion. The number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Based on our data, PET scanning may be not be efficient to identify the primary sites. Other studies have similarly concluded that CT scans may be more useful than PET scans for determining the primary lesions of a bone metastasis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our data, PET scanning may be not be efficient to identify the primary sites. Other studies have similarly concluded that CT scans may be more useful than PET scans for determining the primary lesions of a bone metastasis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 6,539 cancer patients were registered in the Kagoshima University cancer registry between 2007 and 2011; 209 patients had bone metastases. In this retrospective study, we reviewed the medical records and images of 145 patients with metastatic bone tumors who were referred to the Department of Orthopaedic Surgery, Kagoshima University Hospital between 2007 and 2011 as previously reported (5). The patients included 81 men and 64 women with a mean age of 65 years (range, 29-87 years).…”
Section: Methodsmentioning
confidence: 99%
“…SREs include radiotherapy, pathological fractures, spinal cord compression, orthopedic surgery and hypercalcemia. SREs affect not only the prognosis but also the activities of daily living (6). However, to the best of our knowledge, there are currently no reports evaluating the risk factors for SREs at NSCLC diagnosis.…”
Section: Introductionmentioning
confidence: 94%